Justice in the Income Tax Collection on Sale-Purchase - Dewi Fortuna Limurti (Universitas Lampung, 2022)
Income tax for land and buildings purchase in Indonesia is regulated in Law Number 36 of 2008 regarding Income tax. This law stipulates that one of the tax object’s profits comes from land and building sale-purchase. The research would emphasise that income tax comes from other profits instead of transactions or gross prices. This research uses a normative juridical method. “Profits” has an important note in Income Tax’s calculation in the land and building sale-purchase process. Income taxes are collected by calculating the transfer value’s gross amount rather than profits. This calculation violates the Income-tax Law and is highly burdensome for taxpayers. Therefore, it tarnishes the sense of justice in such tax collection and disharmony between the law and its implementation.